Production and industrial performance of small fish slaughterhouses in western Paraná (Research, Society and Development, 2022)
The western region of Paraná stands out in Brazilian fish farming as the largest center of fish production in ponds and industrialization for fillet production, concentrating 24 small, medium, and large fish slaughterhouses. The general objective of the research was to survey the technical parameters of the industrialization of tilapia in six small-scale slaughterhouses in western Paraná. Among the specific objectives: a) survey of the volume of processed fish and fillets produced; b) obtaining labor use and yield parameters; c) evaluate the purchase of raw material and the sale of fillets; and d) verify aspects about transportation logistics. The parameters evaluated brought important technical subsidies, which demonstrate that small industrial plants are an important instrument for the outflow of aquaculture production. The pisciculture in the cities of Toledo, Marechal Candido Rondon, Pato Bragado, and Ouro Verde do Oeste in the western region of Paraná generates an estimated annual income of R$ 71,039,430.00 which provides income to fish farmers, whether they are linked as partners or even independent, and can be considered an important vector of development in the cities of the region, being an emerging agro-industrial chain that provides income generation, employment, and diversification of agricultural production.